1995
DOI: 10.1016/0029-7844(95)00069-4
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for the prenatal diagnosis of classic bladder exstrophy

Abstract: The prenatal diagnosis of bladder exstrophy should be considered any time the bladder is not visualized or any of the aforementioned factors are noted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
52
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(57 citation statements)
references
References 6 publications
2
52
0
3
Order By: Relevance
“…However, most prenatal reports describe detection of fetuses with CE, due to the severity and the high frequency of NTDs associated with this phenotype. 20 The disproportion of barely diagnosed milder but much more prevalent BEEC phenotypes could be due to the fact that prenatal ultrasound focuses more on imaging of NTDs than on the full urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…However, most prenatal reports describe detection of fetuses with CE, due to the severity and the high frequency of NTDs associated with this phenotype. 20 The disproportion of barely diagnosed milder but much more prevalent BEEC phenotypes could be due to the fact that prenatal ultrasound focuses more on imaging of NTDs than on the full urinary bladder.…”
Section: Discussionmentioning
confidence: 99%
“…A limited number of cases of prenatally diagnosed bladder exstrophy have been reported in the English literature during the last 15 years (Table 1) [5][6][7][8][9][10][11][12][13] . Usual findings include nonvisualization of the fetal bladder, low insertion of the umbilicus, pubic bone diastasis, epispadias and small genitals with normal kidneys and normal amniotic fluid volume.…”
Section: Discussionmentioning
confidence: 99%
“…Cacciari and collaborators 5 summarize 10 case reports in which a nonvisualized bladder, normal kidneys and low umbilical cord insertion were found in all cases. Gearhart and coworkers 12 analyzed retrospectively prenatal ultrasounds in 25 pregnancies and found that the diagnosis of bladder exstrophy could be made in 67% of the cases. A non-visible bladder was the most common finding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations